Influenza Virus Vaccines: Lessons from the 2009 H1N1 pandemic - Broadbent, Andrew J. (2011)
Reflecting on the 2009 H1N1 pandemic, we summarize lessons regarding influenza vaccines that can be applied in the future. The two major challenges to vaccination during the 2009 H1N1 pandemic were timing and availability of vaccine. Vaccines were, however, well-tolerated and immunogenic, with inactivated vaccines containing 15μg of HA generally inducing antibody titers ≥1:40 in adults within 2 weeks of the administration of a single dose. Moreover, the use of oil-in-water adjuvants in Europe permitted dose- reduction, with vaccines containing as little as 3.75 or 7.5μg HA being immunogenic. Case-control studies demonstrated that monovalent 2009 H1N1 vaccines were effective in preventing infection with the 2009 H1N1 virus, but preliminary data suggests that it is important for individuals to be re-immunized annually.